Misadventuresof the great North American Businessmen in the Amazon - Dourojeanni, Marc J. (2021)
Between 1927 and 1982, three large forestry (rubber and forest plantation) and agricultural enterprises were developed in the Amazon by important US businessmen. These were idealized byHenry Ford and Daniel Ludwig in Brazil and Robert G. LeTourneau in Peru. None of those projects lasted even 20 years, and all three failed miserably. But they were directly and indirectly responsible for significant deforestation. The lack of planning and knowledge of the local reality explain in a large extent these results. The consequences of these initiatives are mentioned and it is noted that, contrary to what is often believed, the government development plans of Brazil and Peru, in the same period of time, had incomparably more serious environmental implications.